2019
DOI: 10.3390/foods8110549
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Validating a Method for Separating Flavonoid Isomers in Common Buckwheat Sprouts Using HPLC-PDA

Abstract: Buckwheat sprouts that are synthesized during the germination process are rich in flavonoids, including orientin, vitexin, rutin, and their isomers (isoorientin, isovitexin, and quercetin-3-O-robinobioside, respectively). The purpose of this study was to optimize and validate an analytical method for separating flavonoid isomers in common buckwheat sprout extract (CSE). Factors, such as range, linearity, precision, accuracy, limit of detection, and limit of quantification, were evaluated for each standard usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
1
20
0
2
Order By: Relevance
“…Aglycones are more potent antioxidants than corresponding glycosides, but the glucose portion can enhance the bioavailability of compounds [ 49 ]. Isomers of flavone 6- C- glycosides and flavone 8- C- glycosides were differentiated in buckwheat sprouts [ 50 ]. In our study, luteolin 6- C- hexoside and luteolin 8- C- hexoside were found in buckwheat honey from Poland.…”
Section: Resultsmentioning
confidence: 99%
“…Aglycones are more potent antioxidants than corresponding glycosides, but the glucose portion can enhance the bioavailability of compounds [ 49 ]. Isomers of flavone 6- C- glycosides and flavone 8- C- glycosides were differentiated in buckwheat sprouts [ 50 ]. In our study, luteolin 6- C- hexoside and luteolin 8- C- hexoside were found in buckwheat honey from Poland.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, acetonitrile has a higher elution strength, faster retention time, and lower viscosity than methanol for PR-LC. Therefore, acetonitrile allows a short analysis time and high performance (Jang et al, 2019;Welch et al, 2009).…”
Section: Analytical Methods For Soy Isoflavones Separationmentioning
confidence: 99%
“…In general, higher column oven temperatures improve separation and reduce analysis time but restrict the column lifetime and stability of analyzed compounds such as isoflavone glucosides (Mathias et al, 2006). Simultaneous analyses of the flavone and flavonol isomers showed good separation when the temperature of the column oven was 40°C rather than 20°C (Jang et al, 2019). Isoflavones, however, had the highest resolution at 25°C rather than 40°C (Baranowska and Magiera, 2011).…”
Section: Analytical Methods For Soy Isoflavones Separationmentioning
confidence: 99%
“…Analytical studies regarding the quantification of isovitexin from other plant sources such as buckwheat sprouts have already been established [21]. This compound was also found and analyzed in plants such as Passiflora, pigeon pea, wheat leaves, mimosa, bamboo; it was also screened as a bioactive integrant [13,[22][23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%